Múltiplos aprendizados no ensino de frações e números decimais na educação básica - Suzano, Geyson (2018)
The proposal of this work is to make the rescue of elementary education in Basic Education. The initial idea is to make a history of fractions and decimals, identifying when and how the first records arose and from which need were introduced into societies. From there will be a presentation on the teaching of fraction in the present and how are the indices relative to Brazil. In order to understand this process, a qualitative diagnosis will be presented in this work with teachers of Early Childhood Education and Elementary Education (1st Phase) on time of action, formation in Mathematics and formation in fractions and decimals, among others. It will be done an analysis of specific questionnaires, applied to 5th and 9th grade students of elementary and the third grade of high school, with specific questions of models applied in the SAEB (Basic Education Assessment System) with the respective descriptors of the contents studied. Next, the answers given by the students will be discussed. This paper also proposes an intervention for the teaching of fraction with exercises and discussions of possible solutions to facilitate the learning of the content.